RELATIONSHIP TO CUSTOM LAW AND NATIONAL LAW TOWARDS RESTORATIVE JUSTICE - Fatmawati, Irma; Fikri, Rahul Ardian; Siregar, Mhd Azhali; Mawarni, Senja (Proceeding International Conference of Science Technology and Social Humanities, 2023)
The assessment of governance and the distribution of justice in Indonesia is a crucial topic to discuss. Firstly, because Indonesian society is diverse and heterogeneous. Both, the complexity of laws and issues surrounding the terms 'lex' (legislation, regulations) and 'ius' (law, recht). And thirdly, the opinion of Apeldoorn that there is law outside of legislation. The Republic of Indonesia is a legal state (rechtsstaat). In this regard, the state should ensure the enforcement of justice by implementing and upholding existing laws, including customary law. This perspective of legal centralism is assumed to signal the demise of "nonstate" judiciary. However, behind the Principle of Judicial Power Implementation by State Courts, there exists an "unwritten constitution," which is the people' s will regarding justice in the name of the law that exists in society. Whether one likes it or not, non-state judiciary will emerge as a manifestation of the need and legal awareness regarding order and tranquility that cannot always be achieved by state judicial bodies. In this study, the adopted legal concept refers to the fact that outside of state courts, there are also non-formal judicial systems that operate based on customary laws within the community.